The Influence of Learning Styles on the Learning Outcomes of IPS Students Semester II of PGSD Uhkbpnp Study Program - Napitupulu, Rio Parsaoran; Sidabutar, Yanti Arasi (PT Inovasi Pratama Internasional, 2024)
This study aims to determine the effect of learning styles on the learning outcomes of students of the second semester of the Elementary School Teacher Education Study Program, UHKBPNP. This study is a quantitative study that is correlational in nature, which involves a variable that is related between one variable and another. Location of the study This research will be conducted at HKBP Nommensen University, PEmatangsiantar on students of the second semester of the Elementary School Teacher Education Study Program. The data collection technique used is the Learning Style Questionnaire and Documentation. The data analysis technique uses statistical data with the product moment correlation formula, namely the correlation test used to determine the degree of closeness of the relationship between 2 variables with interval and ratio scales. In testing this prerequisite test, IBM SPSS is used. The results of the calculation of the analysis of variance on the differences in social studies learning outcomes between students who have a visual learning style and an auditory learning style with an average = 76.28 and = 70.35. Based on F h = 64.80 and the table value for a= 0.05 with dk (1) it is obtained F t = 3.97 so that it can be stated that F h (64.80) > F t (3.97). Thus the research findings conclude the research hypothesis which states: the learning outcomes of social studies students who have a visual learning style are higher than the learning outcomes of students who have an auditory learning style at a confidence level a= 0.05 has been proven to be true.